2016
DOI: 10.1016/j.ocecoaman.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Lifeguard assistance at Spanish Mediterranean beaches: Jellyfish prevail and proposals for improving risk management

Abstract: 14Although beaches can be hazardous environments, few studies have identified injuries 15 in broad coastal areas. We performed a retrospective descriptive study of injuries and Spanish Mediterranean beaches could be described as low risk, we propose measures to 40 facilitate a precautionary management to prevent injuries based on a real-time beach 41 assistance database of injuries to identify high-incidence assistance categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
(60 reference statements)
0
16
1
2
Order By: Relevance
“…In recent years, many studies have suggested that jellyfish populations are increasing in some areas of the world as a consequence of a combination of several factors, such as overfishing, acidification and global warming (Richardson et al, 2009;Purcell et al, 2007Purcell et al, , 2012, but see Condon et al, 2012), and these booms might cause public health issues. For instance, the number of jellyfish stings along the Mediterranean coast increased by 50% from 2010 to 2012, reaching a total of 118,346 people stung (Bordehore et al, 2016) that far exceeded previous estimations of >14,000 people receiving medical treatment on the south and east Spanish coasts in August 2006 (Pingree and Abend, 2006). This huge number of people affected is an increasing problem with important socioeconomic costs (Mills, 2001;Purcell et al, 2007;Canepa et al, 2014;de Donno et al, 2014;Nunes et al, 2015;Ghermandi et al, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…In recent years, many studies have suggested that jellyfish populations are increasing in some areas of the world as a consequence of a combination of several factors, such as overfishing, acidification and global warming (Richardson et al, 2009;Purcell et al, 2007Purcell et al, , 2012, but see Condon et al, 2012), and these booms might cause public health issues. For instance, the number of jellyfish stings along the Mediterranean coast increased by 50% from 2010 to 2012, reaching a total of 118,346 people stung (Bordehore et al, 2016) that far exceeded previous estimations of >14,000 people receiving medical treatment on the south and east Spanish coasts in August 2006 (Pingree and Abend, 2006). This huge number of people affected is an increasing problem with important socioeconomic costs (Mills, 2001;Purcell et al, 2007;Canepa et al, 2014;de Donno et al, 2014;Nunes et al, 2015;Ghermandi et al, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…In areas around the world dramatic increases in the number and density of scyphozoan species has resulted in fishery collapses and caused significant losses to aquaculture stocks [ 21 , 22 ]. Cubozoans, a family of box shaped cnidarians which often occur in less dense aggregations but are known for their highly venomous sting, have caused millions of dollars in lost tourist revenue in several different geographical locations such as Waikiki beach Hawaii, Queensland Australia and the Mediterranean coast [ 23 25 ]. However, despite these implications, there is a lack of data on distribution, density and spatial and temporal patterns for these marine invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these gelatinous organisms on beaches frequented by people is a significant hazard to regular coastal activities, such as fishing, 1 but also to recreational activities. 2 They may also constitute a significant public health risk. 3,4 They also compete with fish for food.…”
Section: Introductionmentioning
confidence: 99%